Investigation on the dynamic properties of propeller structure with different number of blades - Abdullah, N. A. Z.; Brapakaran, P.; M. S. M., Sani; Marcel, M. W.; Agung, E. H. (IOP Publishing, 2020)
A propeller is mainly used for propelling the movement for an aircraft or ship. As it gives major contribution towards the performance of an aircraft or ship, study on propeller structure has become popular. In this study, the dynamic or modal characteristics of propeller structure with different number of blade of the same design are investigated. Modal properties of two blades, three blades and four blades propeller that are obtained through computational analysis are compared after validation of three blades propeller is conducted. It has been observed that the four blades propeller has the lowest nominal value of natural frequencies and shows most mode shapes deflection. The results confirm that as the propeller has more number of blades, it will produce more energy and hence has lower natural frequency.